Efficient one-pot radiosynthesis of the 11C-labeled aquaporin-4 inhibitor TGN-020 - Kazunori Kawamura; Katsushi Kumata; Tomoteru Yamasaki; Masanao Ogawa; Yusuke Kurihara; Nobuki Nengaki; Yukimi Nakamura; Maiko Ono; Yuhei Takado; Hironaka Igarashi; Ming-Rong Zhang (EJNMMI Radiopharmacy and Chemistry)
Abstract Background [11C]TGN-020 has been developed as a positron emission tomography (PET) tracer for imaging aquaporin-4 (AQP4) in the brain and used in clinical studies. Previously, [11C]TGN-020 was synthesized through the acylation of [11C]nicotinic acid, produced by the reaction of 3-bromopyridine and n-butyllithium with [11C]CO2, with 2-amino-1,3,4-thiadiazole. In this study, to enhance the automated radiosynthesis efficiency of [11C]TGN-020, we optimized its radiosynthesis procedure using our in-house developed 11C-labeling synthesizer. Results [11C]TGN-020 was synthesized via direct [11C]CO2 fixation using n-butyllithium and 3-bromopyridine in tetrahydrofuran, followed by treatment of lithium [11C]nicotinic acetate with isobutyl chloroformate and subsequent acylation with 2-amino-1,3,4-thiadiazole in the presence of N,N-diisopropylethylamine. The optimized process significantly improved the radiosynthesis efficiency of [11C]TGN-020, achieving a high radiochemical yield based on [11C]CO2 (610‒1700 MBq, 2.8 ± 0.7%) at the end of synthesis (n = 12) and molar activity (A m) of 160–360 GBq/μmol at the end of synthesis (n = 5). The radiosynthesis time and radiochemical purity were approximately 60 min and > 95% (n = 12), respectively. PET studies based on [11C]TGN-020 with different A m values were performed using healthy rats. The radioactive uptake of [11C]TGN-020 with high A m in the cerebral cortex was slightly higher than that with low A m. Conclusions [11C]TGN-020 with high A m was obtained in reproducible radiochemical yield. Overall, the proposed optimization process for the radiosynthesis of [11C]TGN-020 can facilitate its application as a PET radiopharmaceutical for clinical use.